NPK CONCENTRATION IN LIQUID MAGGOT FERTILIZER MADE FROM DIFFERENT ORGANIC RESOURCES ANALYZED - Rani Yosilia; Ade Lenty Hoya; Muhammad Fahmi Erlangga; Marlina Kamelia; Triawan Alkausar (UPT Publication and Journal Management, Islamic University of Kalimantan, 2023)
The overuse of chemical fertilizers can have detrimental effects on soil quality. It is important for farmers to find sustainable alternatives. One possible solution being explored is the use of liquid maggot derived from organic sources. This study aimed to determine the most suitable composition that fulfills plant needs and follows established guidelines. The research approach employed a qualitative descriptive method to assess the impacts of three treatments using different types of organic matter: fruit waste, restaurant waste, and palm oil cake. Phosphorus and potassium concentrations were determined through MP-AES analysis while nitrogen content was measured using the Kjeldahl method. The findings revealed that only the treatments involving fruit waste and restaurant waste met the recommended potassium levels. However, these treatments fell short of meeting requirements for other essential nutrients. As a result, additional research is needed to assess nutrient concentrations in different organic substances.